Developing Biomarkers of Rice Bran and Navy Bean Intake via Integrated Metabolomics from Infants, Children and Adults for Association with Gut Health Properties. (29th May 2020) - Ryan, Elizabeth; Baxter, Bridget; Li, Katherine; Wolfe, Lisa; Yao, Linxing; Broecling, Corey; Borreson, Erica; Zhang, Lei; Zarei, Iman; Beale, Melanie; Rao, Sangeeta; Smith, Hillary; et al.
Abstract: Objectives: Self-reporting methods for dietary exposure are error-prone and have had limited impact to identify food components that mitigate disease risk. The purpose of this study was to use non-targeted and targeted metabolomics from feeding trials with rice bran and navy beans for the identification of dietary biomarkers across the lifespan. Methods: Prepared meals/snacks, and biological samples from randomized-controlled trials performed in 50 infants, 38 children and 49 adults were utilized in this study. Diet groups were placebo control, rice bran, cooked navy bean powder, or a combination of rice bran/navy beans with increasing daily doses by age group and for duration of 4, 12 or 24 weeks per protocol. Plasma/dried blood spots, urine or stool samples were collected at a baseline, midpoint and endpoint. Non-targeted profiling was performed with UPLC-MS/MS, and metabolite quantification by LC-triple-quadropole (LC-QQQ-MS). A linear mixed model to compare between time points in each group was performed using SAS. Results: The plasma/blood metabolomes contained between 771–1001 metabolites and showed variation in ∼20–30% of the profile following intervention. Fold changes over time and fold-differences in metabolite abundance were assessed by age ( P  < 0.05). There were 10–20 candidate identified from metabolomics across studies and with relevance to rice bran and/or navy bean were applied for targeted assay development. Food metabolomes confirmed metabolite origins and the host and microbial metabolism. Candidate metabolites included pipecolate, S-methlycysteine, S-methylcysteine sulfoxide, trigonelline, N-methyl-pipecolate, pyridoxal, 2-hydroxyhippurate, apigenin, xanthurenate, chiro-inositol, and salicylate. Inter-individual variation was reported across studies, ages and dietary patterns. Conclusions: Dietary biomarkers for rice bran and/or navy bean intake merit additional selection criteria from non-targeted metabolomics. Targeted assays will need validation in larger cohort investigations using cross-over study designs and diverse dietary patterns. Funding Sources: This work was supported by a grant from the National Institute of Foods and Agriculture-U.S Department of Agriculture (NIFA-USDA).